Control de un motor ac en cuatro cuadrantes con sistema scada - Caguana Coba, Lenin Wagner (2022)
The project carried out on “CONTROL OF AN AC MOTOR IN FOUR QUADRANTS WITH SCADA SYSTEM” refers to the specific applications of a control system. This research paper presents the design of a SCADA system, for measurements of electrical parameters of the AC motor in four quadrants, with an integration of equipment through an industrial network (Modbus RS-485). A display screen was designed, for the design of HMI environments, monitoring was carried out on the speed, power and torque variables and the function performed by each device relevant to the design of the SCADA system. As a result of the implementation of the system there is a better development of the student through the human-machine interface, and through the standards.